Selling all good: how small new entrants can compete. Issue 3 (12th September 2016) - Collins, Eva; Kearins, Kate; Tregidga, Helen; Bowden, Stephen
Abstract : Synopsis: Chris Morrison and two partners introduced the first Fairtrade bananas in New Zealand in a bid to improve the social and environmental impacts of banana consumption. The trio started All Good Bananas in 2010. Using social media as a key marketing tool, the startup had grown to take a 5 percent market share in a fiercely competitive industry dominated by big players. In 2012, the entrepreneurs needed to decide the best way to increase sales of ethically sourced products under the All Good brand. Should they expand their share of the banana market or diversify into drinks? Research methodology: The case is primarily based on tape-recorded interviews by the authors with the founding entrepreneur and three employees of All Good from May to July 2012 and an analysis of the company's website and social media activities. Other publicly available information sources were drawn upon, and a discussion held with a New Zealand national grocery chain CEO. Relevant courses and levels: This case has been written for use in classes in undergraduate and graduate level entrepreneurship, strategic management and sustainability. The case can be used to illustrate how very small resource-constrained startups can compete in an industry dominated by large multinational corporations, and how Fairtrade might provide a worthy differentiation focus. It is open to a consideration of judo economics. While several of the questions ask students to consider the New Zealand context in which this case is set, knowledge of New Zealand and the various industries beyond what is offered in the case is not necessary. Theoretical bases: At a broad level the case illustrates how a small, resource-constrained startup can compete against much, much larger players through a niche Fairtrade product focus and the use of alternative marketing strategies such as guerrilla marketing and social media. In relation to the competitive dynamics within an industry, this case can be used to illustrate the concept of judo economics (also referred to as judo strategy). Both the utility and potential limits of judo economics can be demonstrated through the case by considering current activities and potential future dynamics.